Women's Empowerment in Agricultural Governance (WEAGov) technical workshop: India pilot study - Ragasa, Catherine; Kyle, Jordan; Yasmin, Sabina; Pande, Harshita; Basu, Sampurna; Sharma, Aanshi (CGIAR System Organization, 2024)
Gender Equality research initiative Gender Equality (HER+) is a One CGIAR Research Initiative seeking to address the following four dimensions of gender inequality in agrifood systems: o Women’s lack of agency or limited ability to define and act on goals, make decisions that matter to them, and participate in the economy and in public life; o Women’s lack of access to and control over resources; o Social norms that discriminate based on gender; and o Policies and governance that fail to include and benefit women.